Canadian Association of Gastroenterology Clinical Practice Guideline for the Management of Luminal Crohn's Disease. Issue 3 (10th July 2018) - Panaccione, Remo; Steinhart, A Hillary; Bressler, Brian; Khanna, Reena; Marshall, John K; Targownik, Laura; Afif, Waqqas; Bitton, Alain; Borgaonkar, Mark; Chauhan, Usha; Halloran, Brendan; Jones, Jennifer; et al.
Abstract: Background & Aims: Crohn's disease (CD) is a lifelong illness with substantial morbidity, although new therapies and treatment paradigms have been developed. We provide guidance for treatment of ambulatory patients with mild to severe active luminal CD. Methods: We performed a systematic review to identify published studies of the management of CD. The quality of evidence and strength of recommendations were rated according to the Grading of Recommendation Assessment, Development and Evaluation (GRADE) approach. Statements were developed through an iterative online platform and then finalized and voted on by a group of specialists. Results: The consensus includes 41 statements focused on 6 main drug classes: antibiotics, 5-aminosalicylate, corticosteroids, immunosuppressants, biologic therapies, and other therapies. The group suggested against the use of antibiotics or 5-aminosalicylate as induction or maintenance therapies. Corticosteroid therapies (including budesonide) can be used as induction, but not maintenance therapies. Among immunosuppressants, thiopurines should not be used for induction, but can be used for maintenance therapy for selected low-risk patients. Parenteral methotrexate was proposed for induction and maintenance therapy in patients with corticosteroid-dependent CD. Biologic agents, including tumor necrosis factor antagonists, vedolizumab, and ustekinumab, were recommended for patients failed by conventional induction therapies and as maintenance therapy. The consensus group was unable to clearly define the role of concomitant immunosuppressant therapies in initiation of treatment with a biologic agent. Conclusions: Optimal management of CD requires careful patient assessment, acknowledgement of patient preferences, evidence-based use of existing therapies, and thorough assessment to define treatment success.